Brain Mitochondrial Impairment in Early‐Onset Parkinson's Disease With or Without PINK1 Mutation. Issue 3 (2nd January 2020) - Rango, Mario; Dossi, Gabriele; Squarcina, Letizia; Bonifati, Cristiana
Abstract: Background: PINK1 mutations are likely to affect mitochondrial function. The objective of this study was to study brain mitochondrial function in patients with early‐onset Parkinson's disease, with or without PINK1 mutations. Methods: We investigated brain intracellular pH, mitochondrial activity, and energetics with functional magnetic resonance spectroscopy in patients with early‐onset Parkinson's disease with PINK1 mutations (n = 10), early‐onset Parkinson's disease without PINK1 mutations (n = 10), and healthy sex‐ and age‐matched subjects (n = 20). We measured peak areas of phosphocreatine and beta adenosine triphosphate. Results: The EOPD‐ group had normal PCr + βATP contents at rest ( P = NS) and under activation ( P = NS), but reduced contents during recovery ( P < 0.001). The EOPD+ group had abnormal PCr + βATP contents at rest ( P < 0.001) and during activation ( P < 0.001); during recovery, the contents only partially recovered ( P < 0.001). Brain intracellular pH alterations were more severe with EOPD+ than with EOPD−. Conclusions: Brain mitochondrial impairments were similar in early‐onset Parkinson's disease without PINK1 mutations and late‐onset Parkinson's disease. However, mitochondrial impairments were more severe in early‐onset Parkinson's disease with PINK1 mutations. © 2020 International Parkinson and Movement Disorder Society